2011
DOI: 10.3168/jds.2010-4084
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with hair loss, ulceration, and swelling at the hock in freestall-housed UK dairy herds

Abstract: The objective of this study was to identify the risk factors associated with 3 presentations of hock lesions (hair loss, ulceration, and swelling) in freestall-housed lactating cattle. By independent identification and scoring of, and analysis of the factors associated with, hair loss, ulceration, and swelling, the aim was to identify whether risk factors were common to all 3, or differed among the presentations. A cross-sectional study was conducted on 76 herds in the UK during the winter housing period of 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
101
5
9

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(136 citation statements)
references
References 23 publications
21
101
5
9
Order By: Relevance
“…Furthermore, it speaks in favour of the hypothesis, that underlying causes for H and W are the same, but need to be stronger or applied over a longer time period to cause the more severe alteration. On the other hand, S were oftentimes separated from H and W at the same location with more detailed clustering, which is in line with Potterton et al (2011a) who found several risk factors in common for H and W at the hocks, but only one common risk for H and S at the same location.…”
Section: Clusteringsupporting
confidence: 87%
See 3 more Smart Citations
“…Furthermore, it speaks in favour of the hypothesis, that underlying causes for H and W are the same, but need to be stronger or applied over a longer time period to cause the more severe alteration. On the other hand, S were oftentimes separated from H and W at the same location with more detailed clustering, which is in line with Potterton et al (2011a) who found several risk factors in common for H and W at the hocks, but only one common risk for H and S at the same location.…”
Section: Clusteringsupporting
confidence: 87%
“…In Denmark as well as Canada, the combined prevalence for H, W and S at the hock was 47% (Burow et al, 2013;Zaffino Heyerhoff et al, 2014). When looking at the different alterations at the tarsal joint, separately, much higher prevalences have been found in the United Kingdom for S (100%) as well as H (92%), but W (18%) was in a comparable range (Potterton et al, 2011a). In a Norwegian study on the other hand, H (53%) and W (6%) were in a comparable range, but prevalence of S was considerably lower (1%) (Kielland et al, 2009).…”
Section: Distribution Of Alterationsmentioning
confidence: 94%
See 2 more Smart Citations
“…For British free-stall and straw-pen herds, with more than 50 cows, it has been described that hock damage (including hair loss and lesions) and swellings decrease with increasing number of months with summer grazing (Rutherford et al, 2008). Further, in the United Kingdom, free-stall herds with an average of 162 cows, hair loss and to some extent ulcerations at the hock joint increased with increasing number of days of indoor winter housing (Potterton et al, 2011). No study has as yet tested the impact of daily grazing hours for such herds.…”
Section: Introductionmentioning
confidence: 99%